Escrevivências de professoras negras: caminhos insurgentes para as questões étnico-raciais na escola - Queiroz, Gleice Melo Silva (2023)
This dissertation aims to understand how the body-territory Writings of black teachers can highlight decolonial propositions for an anti-racist pedagogy, through the encounter starting from me, from my body, in socialization with the teachers, Aline Barbosa, Fabiana Batista, Jamile Dias, Nilldinha Odara and Sara Silva, from the municipal network of Feira de Santana - Bahia. Based on the methodology of empirical research, focused on qualitative analysis, the device of Writings was used as a theoretical-methodological contribution, which brings an Afro-feminine counter-narrative to the challenges of being a woman, black and a teacher and, above all, shares experiences of actions with racial themes at school. With the counter-hegemonic reflections and provocations of the studies by Conceição Evaristo (2005) about E Escritovências; Eduardo Miranda (2014) on the Body-territory; Maldonado-Torres (2020) and Catherine Walsh (2014) regarding Decoloniality and a discussion that covers Black Feminism, with theorists Lélia González (1988), Sueli Carneiro (2005), bell hooks (2017), also a highlight for Anti-Racist Pedagogy, as discussed by Nilma Gomes (2005) and Petronilha Silva (2005), the dissertation focuses on black teachers, as the subjects of the research, making visible these voices, experiences and writings that are forged through resistance and insurgency. In this sense, the meetings that I called Roda para Cre(vi)ver took place, the creations of drawing and photographic artifacts and the writings of self/us that depart from the Writing Body-territory, an analysis category developed in this research. These contributions enhanced in the collective among black women teachers, also reflect the anchoring with the field of Sociopoetics, in the lived moment of counter-analysis, coined by Jacques Gauthier (2012). In view of these collective constructions, I highlight the transgression of black teachers, as protagonists of their/our history, which presents writing as a driving wheel of pedagogical power to (re)educate ethnic-racial relations, emerging paths for implementing racial educational laws.